Aproximaciones al gobierno corporativoen Colombia: incursión y desarrollos actuales. Perspectivas de aplicación en el Mercado de Valores - Vélez Pachón, Federico (2023)
This paper presents a simple framework that brings together basic ideas about Corporate Governance and its current normative regime in Colombia. The author focuses on the influence of corporate governance on the agents that participate in the Stock Market (emitting agents and investors). Specifically, the paper discusses the role the legal and regulatory system in Colombia plays in the development of Corporate Governance. Based on current literature and on the legal environment, the article shows some of the ways in which Corporate Governance can be used in the Colombian Stock Market as a tool that makes the sectorís stability, security, and confidence possible.